If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9x + -7 = -6x + 6 + -7 Reorder the terms: -7 + 3x + -9x = -6x + 6 + -7 Combine like terms: 3x + -9x = -6x -7 + -6x = -6x + 6 + -7 Reorder the terms: -7 + -6x = 6 + -7 + -6x Combine like terms: 6 + -7 = -1 -7 + -6x = -1 + -6x Add '6x' to each side of the equation. -7 + -6x + 6x = -1 + -6x + 6x Combine like terms: -6x + 6x = 0 -7 + 0 = -1 + -6x + 6x -7 = -1 + -6x + 6x Combine like terms: -6x + 6x = 0 -7 = -1 + 0 -7 = -1 Solving -7 = -1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -1/2(8x+4)+1/9(54x+45) | | y=(2x^2)/((n^3)+3) | | -6-2n=-(n-2) | | -z+1=7z-13 | | z-1=7z-13 | | X+19+2x=-15-2x-21 | | y/11=10 | | -6(5x-9)+8=-30x+62 | | (15x^2)/(10x) | | y/=10 | | 12y^2+32y-35=0 | | 180=60(x+20)3x | | x-y=73 | | -14p=168 | | 3u+4u-7= | | 12y+32y-35=0 | | -11/8=-3/2n+2 | | -3(1-2r)=9+4r | | 8y-3y+2=-18 | | 2(4-3t)-(-3)=2t | | -2(5-6n)=30+7n | | 3u=4u-7 | | -4n-2=3-8n+5n | | 3/2x+90+2x+3x+x=360 | | 2x+108=180 | | 2x+2/3=3x-4 | | -12.5=15.5q+4(3q-3) | | 11/8=-11/2n+2 | | 1-m/2=7 | | 6g+16=2y+32 | | x-8/7=-9 | | 3x(2x+6)=17+(8x+1) |